Determinant of perceived social impact on community in hosting a sport tourism event - Ambra Abu Bakar; Chung Lehsin; Khairul Anwar Ashar; Gomala Murugappan (2016)
This study is conducted to find out the determinants that affect perceived social impact in hosting sport tourism event. The objectives of this research are to understand the relationship between economic effects, community development, security risk, and perceived social impact. The study was used quantitative method. The methodology that was used in collecting data was a survey design that used convenience sampling technique where questionnaire were distributed. This study will collect 384 responses of questionnaire from selected respondents. In a nutshell, this study will indicate that sport tourism event will influence the perceived social impact in the local community.